Study of comorbidities in chronic obstructive pulmonary disease patients at tertiary health care centre in south Gujarat just in the era of Covid-19 pandemic − a cross-sectional study - Sreerag Varior; Parul Vadgama; Robinkumar Patel; Bhoomika Patel; Jignesh Gengadiya (The Journal of Association of Chest Physicians)
Background: Chronic obstructive pulmonary disease (COPD) can coexist with other diseases that may significantly impact the disease course. In this study, our aim is to study the prevalence of various extrapulmonary comorbid conditions associated with COPD. Method: This is a cross-sectional study, including all COPD patients presenting to Outpatient Department (OPD) and Inpatient Department (IPD) of Respiratory Medicine Department after meeting the inclusion and exclusion criteria. A COPD patient was defined as a smoker or having exposure to noxious gases, with forced expiratory volume in 1 s (FEV1)/forced vital capacity (FVC) <0.7 and comorbidities were defined based on objective laboratory findings and questionnaires. Comorbidities were identified from patient self-reports and disease-specific lab analysis and medication. Results: Among the 200 patients of COPD, hypertension was found to be the most common comorbidity with a prevalence of 44% followed by diabetes mellitus with a prevalence of 28% and then dyslipidaemia 26.5%. The prevalence of ischemic heart disease (8.5%), depression (16.5%), anemia (16%), osteoarthritis (13%), and chronic kidney disease (9.5%) were other comorbidities among the patients. Smoking is the major culprit with an 80.5% prevalence among the patients. Conclusions: Hypertension was the most common comorbidity in our study population. An increasing number of people in any aging population will suffer from multi-morbidity, defined as the presence of two or more chronic conditions, and COPD is present in the majority of multi-morbid patients. Whether or not COPD and comorbid diseases are related, management of the COPD patient must include the identification and treatment of its comorbidities.